Determinantes e consequentes do engajamento do consumidor em comunidades virtuais de marca: proposição e teste empírico de um modelo teórico - Andréia Cássia de Moura (2020)
Initiatives to propose conceptual models containing consumer behavioral and relational variables and engagement are increasing throughout the Marketing literature. Despite the growing studies on consumer engagement in online brand communities, they are still incipient in the sense of validating more comprehensive and integrating conceptual models that treat consumer engagement behavior as a central construct in a nomological network of determinants and consequences. Engagement involving other market players, like other consumers, needs to receive more attention, given that the online brand communities (OBC) are expanding over time. Thus, the present thesis aimed at the empirical validation of a conceptual model conceived through a literature review to explain consumer engagement in online brand communities, contemplating antecedents that are rarely addressed in the literature, as well as consequences and the verification of the effect of moderating variables on the proposed model. For this, the qualitative methodology was adopted - netnography, in order to highlight appropriated constructs and indicators to the object of study. The use of quantitative methodology occurred through a survey applied to a sample of 583 respondents that proved to be suitable for the application of multivariate techniques and Structural Equation Modeling (SEM). The results pointed to the plausibility of the proposed conceptual model. The assumption of the consumer “social identity” and consumer “self-expressiveness” are determinants of “brand community engagement” has been confirmed. Regarding the construct "brand consumer engagement”, the influence of two drives was confirmed - "brand identification " and "brand community engagement", the latter having a stronger impact as a determinant. The constructs “brand loyalty”, “brand value” and “positive word-of-mouth” were revealed, due to the results, as consequences of consumer “brand engagement”. There was also support for the hypothesis of the moderating effect of constructs referring to the value attributed to the brands (utility value versus hedonic value). In the presence of the moderators, the “brand identification” influenced the “brand community engagement”, for the group that uses hedonic brands. In addition, “brand consumer engagement” and its impact on “positive word-of-mouth” was slightly stronger for utility brands than for hedonic brands. Therefore, the innovation of the present study consisted of: 1) verification of the impact of the individual's constructs related to the self (self-concept) and its social identity; 2) the verification and confirmation of the effect of new moderating variables on the structural model; 3) the application of Netnography to highlight proposed constructs and indicators. The support of the data to the consequent constructs also contributed to the understanding of the engagement reflexes. Based on the results, relevant theoretical and managerial implications were found in the body of the thesis. This thesis presented the following contributions: i) external validation of a more comprehensive and integrating model of consumer engagement in OBC; ii) new scales validated for constructs that were adapted to the OBC context; iii) a model capable of being replicated in similar contexts, requiring the researcher to adopt adaptations whenever necessary. constructs of the individual regarding the self (self-concept) and its social identity; 2) the verification and confirmation of the effect of new moderating variables on the structural model; 3) the application of Netnography to highlight proposed constructs and indicators.